Gatekeepers of the Arab Past : Historians and History Writing in Twentieth-Century Egypt - Di-Capua, Yoav, 1970- (Book collections on Project MUSE., 2009)
Yoav Di-Capua explores Egyptian historical thought, examines the careers of numerous critical historians & traces the uneasy relationship of this tradition with colonial forms of knowledge as well as with the postcolonial state.